Cartas de Parker como parte do saber profissional do professor que ensinava matemática a partir da Revista de Ensino (1902 – 1903) - Andrade, Mariana Nunes (2022)
This work is the result of a research that aimed to characterize the orientations of Parker's Letters as part of the professional knowledge of the teacher who taught mathematics, from the Revista de Ensino in the period of 1902 and 1903. copies of the Revista de Ensino, which presented guidelines on how the teacher should use Parker's Letters. The understandings adopted to examine the sources were adopted from works such as Valente (2008) and Portela (2014) for an understanding of Parker's Letters; Parker (1909) on teaching numbers; Valente et al. (2017) on the professional knowledge of the teacher who taught mathematics; and Morais, Bertini and Valente (2021) on teaching mathematics and the categories of analysis: sequence, meaning, graduation and exercise and problems. Through the examination carried out from Parker's Letters, it was possible to characterize a sequence of: numbers from Letters 1st to 5th, 15th, 17th and 18th; fraction through the 2nd to 43rd Cards the four operations through the 6th to 48th Cards. In these groups of Letters, it was also identified that in some of them there was only the use of addition (19th, 28th, 29th and 38th), addition and subtraction (31st to 34th), multiplication (46th), division (47th), multiplication and division (11th, 22nd to 24th, 36th). It was possible to establish a graduation, in which the teacher should follow the teaching of contents from observation to action, using pictures, oralization, problems and objects, which at times the teacher manipulated or presented as part of the principles of the method. intuitive. And, the exercises and problems were used in most cases for fixation and in others for the construction of meanings, at times they were worked through oralization and at others through writing. These categories of analysis taken from teaching mathematics make it possible to characterize the guidelines of Parker's Letters as didactic material that is part of the professional knowledge of the teacher who taught mathematics.